Barriers to prompt and effective malaria treatment among the poorest population in Kenya - Chuma, J; Okungu, V; Molyneux, C (BioMed Central, 2010)
Background: Prompt access to effective malaria treatment is central to the success of malaria control worldwide, but few fevers are treated with effective anti-malarials within 24 hours of symptoms onset. The last two decades saw an upsurge of initiatives to improve access to effective malaria treatment in many parts of sub-Saharan Africa. Evidence suggests that the poorest populations remain least likely to seek prompt and effective treatment, but the factors that prevent them from accessing interventions are not well understood. With plans under way to subsidize ACT heavily in Kenya and other parts of Africa, there is urgent need to identify policy actions to promote access among the poor. This paper explores access barriers to effective malaria treatment among the poorest population in four endemic districts in Kenya. Methods: The study was conducted in the poorest areas of four malaria endemic districts in Kenya. Multiple data collection methods were applied including: a cross-sectional survey (n = 708 households); 24 focus group discussions; semi-structured interviews with health workers (n = 34); and patient exit interviews (n = 359). Results: Multiple factors related to affordability, acceptability and availability interact to influence access to prompt and effective treatment. Regarding affordability, about 40 percent of individuals who self-treated using shop-bought drugs and 42 percent who visited a formal health facility reported not having enough money to pay for treatment, and having to adopt coping strategies including borrowing money and getting treatment on credit in order to access care. Other factors influencing affordability were seasonality of illness and income sources, transport costs, and unofficial payments. Regarding acceptability, the major interrelated factors identified were provider patient relationship, patient expectations, beliefs on illness causation, perceived effectiveness of treatment, distrust in the quality of care and poor adherence to treatment regimes. Availability barriers identified were related to facility opening hours, organization of health care services, drug and staff shortages. Conclusions: Ensuring that all individuals suffering from malaria have prompt access to effective treatment remains a challenge for resource contrained health systems. Policy actions to address the multiple barriers of access should be designed around access dimensions, and should include broad interventions to revitalize the public health care system. Unless additional efforts are directed towards addressing access barriers among the poor and vulnerable, malaria will remain a major cause of morbidity and mortality in sub-Saharan Africa.